2010
DOI: 10.1088/1475-7516/2010/01/021
|View full text |Cite
|
Sign up to set email alerts
|

Resolving cosmic neutrino structure: a hybrid neutrinoN-body scheme

Abstract: We present the first simulation capable of resolving the structure of neutrino clustering on Mpc scales. The method combines grid-and particle-based methods and achieves very good accuracy on both small and large scales, while keeping CPU consumption under control. Such simulations are not only ideal for calculating the non-linear matter power spectrum but also particularly relevant for studies of how neutrinos cluster in galaxy-or cluster-sized halos. We perform the largest neutrino Nbody simulation to date, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 19 publications
1
100
0
Order By: Relevance
“…Since cosmological constraints can mainly be derived from moderate and large l-values it means that non-linear corrections must be under control at the percent level. For neutrinos this has already been achieved [70][71][72], but for example baryonic physics can contribute an uncertainty of 10% or more on scale which are relevant for cosmological parameter extraction [109].…”
Section: Weak Lensing Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cosmological constraints can mainly be derived from moderate and large l-values it means that non-linear corrections must be under control at the percent level. For neutrinos this has already been achieved [70][71][72], but for example baryonic physics can contribute an uncertainty of 10% or more on scale which are relevant for cosmological parameter extraction [109].…”
Section: Weak Lensing Surveysmentioning
confidence: 99%
“…Simply treating neutrinos as particles is difficult because the thermal motion introduces noise which completely dominates the behaviour of neutrinos on small scales. However, it has been shown that the matter power spectrum can be computed at the 1% level of precision with neutrinos included, using Nbody techniques [70][71][72]61] (Fig. 4).…”
Section: Non-linear Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrinos are also responsible for dampening the matter power spectrum below their free-streaming scale; see e.g., [23] for a review. This effect, which amounts to a scale dependent power suppression, is straightforward to compute in linear theory [37] and in the non-linear regime via numerical simulations e.g., [38,39,40].…”
Section: Cosmology: Observational Constraints and Degeneraciesmentioning
confidence: 99%
“…[5,6]). At the same time, numerical predictions of the effect of neutrino masses on the clustering of small-scale structures are making a good deal of headway [7,8]. Within one decade, cosmological observations should be able to detect the absolute neutrino mass scale, even if the heaviest mass is close to 0.05 eV.…”
mentioning
confidence: 99%